Salesperson human capital investment and heterogeneous export enterprises performance - Zhao, Yongliang; Ruan, Weihua; Jiang, Yonghong; Rao, Junnan (Journal of Business Economics and Management, 2018)
This paper aims to study the impact of salesperson human capital investment on the export performance of heterogeneous enterprises in China. To distinguish the different effects on the staff level and the management level, we define the human capital investment for the overall salespersons as human capital investment I and the human capital investment for the sales managers as human capital investment II, respectively measured by the salary of the ordinary salespersons and the ratio of expenses to sales. We find that human capital investment I has a significant positive effect on export performance, while human capital investment II shows a “positive U-shaped” relationship with export performance. Considering the heterogeneity of enterprise, the positive effect of human capital investment I is more significant than that of human capital investment II in enterprises with high R&D intensity. Moreover, with the improvement of technology intensity, both the promotion of human capital investment I and human capital investment II would generate greater influence on export performance.